Structural and tribometric characterization of biomimetically inspired synthetic "insect adhesives" - Speidel, Matthias W.; Kleemeier, Malte; Hartwig, Andreas; Rischka, Klaus; Ellermann, Angelika; Daniels, Rolf; Betz, Oliver (Beilstein Journal of Nanotechnology, 2017)
Background: Based on previous chemical analyses of insect tarsal adhesives, we prepared 12 heterogeneous synthetic emulsions mimicking the polar/non-polar principle, analysed their microscopical structure and tested their adhesive, frictional, and rheological properties.Results: The prepared emulsions varied in their consistency from solid rubber-like, over soft elastic, to fluid (watery or oily). With droplet sizes >100 nm, all the emulsions belonged to the common type of macroemulsions. The emulsions of the first generation generally showed broader droplet-size ranges compared with the second generation, especially when less defined components such as petrolatum or waxes were present in the lipophilic fraction of the first generation of emulsions. Some of the prepared emulsions showed a yield point and were Bingham fluids. Tribometric adhesion was tested via probe tack tests. Compared with the "second generation" (containing less viscous components), the "first generation" emulsions were much more adhesive (31–93 mN), a finding attributable to their highly viscous components, i.e., wax, petrolatum, gelatin and poly(vinyl alcohol). In the second generation emulsions, we attained much lower adhesivenesses, ranging between 1–18 mN. The adhesive performance was drastically reduced in the emulsions that contained albumin as the protein component or that lacked protein. Tribometric shear tests were performed at moderate normal loads. Our measured friction forces (4–93 mN in the first and 0.1–5.8 mN in the second generation emulsions) were comparatively low. Differences in shear performance were related to the chemical composition and emulsion structure.Conclusion: By varying their chemical composition, synthetic heterogeneous adhesive emulsions can be adjusted to have diverse consistencies and are able to mimic certain rheological and tribological properties of natural tarsal insect adhesives.
Keywords: adhesion; bionics; emulsion; friction; insects

(untitled) - Beutel, R. G.; Gorb, S. N. (J. Zool. Syst. Evol. Res., 2001)

(untitled) - Edwards, J. S.; Tarkanian, M. (Proc. R. Entomol. Soc. London, Ser. A, 1970)

(untitled) - Dixon, A. F. G.; Croghan, P. C.; Gowing, R. P. (J. Exp. Biol., 1990)

Biological adhesive systems - From nature to technical and medical application - Betz, O. (Adhesive exocrine glands in insects: morphology, ultrastructure, and adhesive secretion, 2010)

(untitled) - Drechsler, P.; Federle, W. (J. Comp. Physiol., A, 2006)

(untitled) - Persson, B. N. J. (J. Adhes. Sci. Technol., 2007)

(untitled) - Dewitz, H. (Pfluegers Arch. Gesamte Physiol. Menschen Tiere, 1884)

(untitled) - Stork, N. E. (J. Exp. Biol., 1980)

(untitled) - Walker, G.; Yule, A. B.; Ratcliffe, J. (J. Zool., 1985)

(untitled) - Walker, G. (Int. J. Adhes. Adhes., 1993)

(untitled) - Lees, A. D.; Hardie, J. (J. Exp. Biol., 1988)

(untitled) - Langer, M. G.; Ruppersberg, J. P.; Gorb, S. (Proc. R. Soc. London, Ser. B, 2004)

Mechanics of adhesion and friction in stick insects and tree frogs - Drechsler, P. H. (University of Würzburg, 2008)

(untitled) - Dirks, J.-H.; Clemente, C. J.; Federle, W. (J. R. Soc., Interface, 2010)

(untitled) - Reitz, M.; Gerhardt, H.; Schmitt, C.; Betz, O.; Albert, K.; Lämmerhofer, M. (Anal. Chim. Acta, 2015)

(untitled) - Gerhardt, H.; Schmitt, C.; Betz, O.; Albert, K.; Lämmerhofer, M. (J. Chromatogr. A, 2015)

(untitled) - Gerhardt, H.; Betz, O.; Albert, K.; Lämmerhofer, M. (J. Chem. Ecol., 2016)

(untitled) - Betz, O.; Verheyden, A. N.; Maurer, A.; Schmitt, C.; Braun, J.; Kowalik, T.; Grunwald, I.; Hartwig, A.; Neuenfeldt, M. (Insect Mol. Biol., 2016)

(untitled) - Geiselhardt, S. F.; Geiselhardt, S.; Peschke, K. (Chemoecology, 2009)

(untitled) - Kölsch, G. (Can. J. Zool., 2000)

(untitled) - Vötsch, W.; Nicholson, G.; Müller, R.; Stierhof, Y.-D.; Gorb, S.; Schwarz, U. (Insect Biochem. Mol. Biol., 2002)

(untitled) - Gorb, S. N. (Philos. Trans. R. Soc. London, Ser. A, 2008)

(untitled) - Federle, W.; Riehle, M.; Curtis, A. S. G.; Full, R. J. (Integr. Comp. Biol., 2002)

(untitled) - Barnes, H. A. (Colloids Surf., A, 1994)

(untitled) - Bibette, J.; Leal Calderon, F.; Poulin, P. (Rep. Prog. Phys., 1999)

(untitled) - Peisker, H.; Gorb, S. N. (J. Exp. Biol., 2012)

Chemical, morphological and biomechanical aspects of tarsal attachment in beetles - Geiselhardt, S. F. (University of Freiburg, 2009)

(untitled) - Geiselhardt, S. F.; Lamm, S.; Gack, C.; Peschke, K. (J. Comp. Physiol., A, 2010)

(untitled) - Douaire, M.; Stephenson, T.; Norton, I. T. (J. Food Eng., 2014)

(untitled) - Farah, M. A.; Oliveira, R. C.; Caldas, J. N.; Rajagopal, K. (J. Pet. Sci. Eng., 2005)

(untitled) - Lee, H. M.; Lee, J. W.; Park, O. O. (J. Colloid Interface Sci., 1997)

Design and Nature IV - Speck, T.; Speck, O. (Process sequences in biomimetic research, 2008)

(untitled) - Derkach, S. R. (Adv. Colloid Interface Sci., 2009)

(untitled) - Pal, R. (Curr. Opin. Colloid Interface Sci., 2011)

(untitled) - Chan, E. P.; Greiner, C.; Arzt, E.; Crosby, A. J. (MRS Bull., 2007)

(untitled) - Gorb, S. N.; Sinha, M.; Peressadko, A.; Daltorio, K. A.; Quinn, R. D. (Bioinspiration Biomimetics, 2007)

(untitled) - Li, W.; Kong, X. H.; Ruan, M.; Ma, F. M.; Jiang, Y. F.; Liu, M. Z.; Chen, Y.; Zuo, X. H. (Philos. Trans. R. Soc. London, Ser. A, 2010)

(untitled) - Flammang, P.; Santos, R. (Interface Focus, 2015)

(untitled) - Gibbs, A.; Pomonis, J. G. (Comp. Biochem. Physiol., Part B: Biochem. Mol. Biol., 1995)

(untitled) - Gibbs, A. (J. Insect Physiol., 2002)

(untitled) - Attygalle, A. B.; Aneshansley, D. J.; Meinwald, J.; Eisner, T. (Zoology (Jena, Ger.), 2000)

(untitled) - Hasenfuss, I. (Zoomorphologie, 1977)

(untitled) - Hasenfuss, I. (Zoomorphology, 1999)

Kleben: Grundlagen, Technologien, Anwendungen - Habenicht, G. (Springer, 2009)

(untitled) - Betz, O.; Kölsch, G. (Arthropod Struct. Dev., 2004)

(untitled) - Jiao, Y.; Gorb, S.; Scherge, M. (J. Exp. Biol., 2000)

(untitled) - Labonte, D.; Federle, F. (Philos. Trans. R. Soc. London, Ser. B, 2015)

(untitled) - Labonte, D.; Federle, W. (Soft Matter, 2015)

(untitled) - Koerner, L.; Gorb, S. N.; Betz, O. (J. Insect Physiol., 2012)

(untitled) - Koerner, L.; Gorb, S. N.; Betz, O. (Zoology, 2012)

Intermolecular and Surface Forces - Israelachvili, J. N. (Academic Press, 2011)

(untitled) - Bhushan, B. (J. Vac. Sci. Technol., B, 2003)

(untitled) - Clemente, C. J.; Federle, W. (Proc. R. Soc. London, Ser. B, 2008)

(untitled) - Bullock, J. M. R.; Drechsler, P.; Federle, W. (J. Exp. Biol., 2008)

(untitled) - Federle, W.; Baumgartner, W.; Hölldobler, B. (J. Exp. Biol., 2004)

Tribology on the small scale - A bottom up approach to friction, lubrication, and wear - Mate, C. M. (Oxford University Press, 2008)

(untitled) - Yoshizawa, H.; Chen, Y. L.; Israelachvili, J. (J. Phys. Chem., 1993)

(untitled) - Ariano, R. (Rubber Chem. Technol., 1930)

(untitled) - Derieux, J. B. (Rubber Chem. Technol., 1935)

(untitled) - Schallamach, A. (Proc. Phys. Soc., London, Sect. B, 1953)

Experimentelle und theoretische Untersuchungen zur Gummireibung in einem großen Geschwindigkeits- und Temperaturbereich unter Berücksichtigung der Reibungswärme - Rieger, H. (Fakultät für Maschinenwesen und Elektrotechnik der Technische Hochschule München, 1968)

(untitled) - Vogel, M. J.; Steen, P. H. (Proc. Natl. Acad. Sci. U. S. A., 2010)

Modern Research and Educational Topics in Microscopy - Gorb, S. N.; Voigt, D.; Gorb, E. V. (Visualisation of small fluid droplets on biological and artifical surfaces using the cryo-SEM approach, 2007)

(untitled) - Hartwig, A.; Meissner, R.; Merten, C.; Schiffels, P.; Wand, P.; Grunwald, I. (J. Adhesion, 2013)

(untitled) - Stefan, J. (Ann. Phys., 1875)